Heart Failure with Perserved Ejection Fraction Current Diagnostic and Therapeutic Approaches - A. A. Shchendrygina; K. A. Zhbanov; E. V. Privalova; A. O. Yusupova; Yu. A. Danilogorskaya; E. Yu. Salakheeva; I. Ya. Sokolova; S. A. Tsatsurova; A. A. Ageeva; Yu. N. Belenkov (Столичная издательская компания, 2021)
Heart failure with preserved ejection fraction (HFpEF) is a syndrome associated with high morbidity and mortality rates. Little progress has been in the treatment of this condition since its introduction some 30 years ago. It's accepted that HFpEF is heterogeneous in many ways, ethologically and phenotypically. The underlying mechanisms of the syndrome are not clear. Recently, it has been shown that the diagnostic criteria for HFpEF lacks sensitivity and specificity. Novel treatment approaches, which were developed based on current HFpEF pathophysiological concepts, did not show either clinical or prognostic benefit for patients. Therefore, there is an urgent need to revise current diagnostic approaches and to further investigate the underlying mechanisms. Recently, two novel diagnostic score systems were proposed: H2PEF and HFA-PEFF. Recently, a number of phase II and III randomized control trials have been completed. Here, the authors discuss the potential novel diagnostic approaches to HFpEF and treatment perspectives.